Oxidative Damages on the Alzheimer's Related-Aβ Peptide Alters Its Ability to Assemble - Clémence Cheignon; Fabrice Collin; Laurent Sabater; Christelle Hureau (MDPI AG, 2023)
Oxidative stress that can lead to oxidation of the amyloid-β (Aβ) peptide is considered a key feature in Alzheimer's disease (AD), influencing the ability of Aβ to assemble into β-sheet rich fibrils that are commonly found in senile plaques of AD patients. The present study aims at investigating the fallouts of Aβ oxidation on the assembly properties of the Aβ peptide. To accomplish this, we performed kinetics and analysis on an oxidized Aβ (oxAβ) peptide, resulting from the attack of reactive oxygen species (ROS) that are formed by the biologically relevant Cu/Aβ/dioxygen/ascorbate system. oxAβ was still able to assemble but displayed ill-defined and small oligomeric assemblies compared to the long and thick β-sheet rich fibrils from the non-oxidized counterpart. In addition, oxAβ does affect the assembly of the parent Aβ peptide. In a mixture of the two peptides, oxAβ has a mainly kinetic effect on the assembly of the Aβ peptide and was able to slow down the formation of Aβ fibril in a wide pH range [6.0-7.4]. However, oxAβ does not change the quantity and morphology of the Aβ fibrils formed to a significant extent. In the presence of copper or zinc di-cations, oxAβ assembled into weakly-structured aggregates rather than short, untangled Cu-Aβ fibrils and long untangled Zn-Aβ fibrils. The delaying effect of oxAβ on metal altered Aβ assembly was also observed. Hence, our results obtained here bring new insights regarding the tight interconnection between (i) ROS production leading to Aβ oxidation and (ii) Aβ assembly, in particular via the modulation of the Aβ assembly by oxAβ. It is the first time that co-assembly of oxAβ and Aβ under various environmental conditions (pH, metal ions ...) are reported.